Beasts of burden, trade, and hierarchy: The long shadow of domestication - Andreas Link (Friedrich-Alexander-Universität Erlangen-Nürnberg, Bavarian Graduate Program in Economics (BGPE), 2023)
This paper studies how the prehistoric geographic distribution of domesticable transport animal species has contributed to shaping differences in development. I identify the historic ranges of the ten animal species that are (1) suitable for domestication and (2) suitable for carrying loads. Based on these ranges, I create a measure of the prehistoric presence of domesticable transport animals around the world. The empirical analysis reveals a strong relationship between the historic presence of domesticable transport animals and the emergence of ancient long-distance trade routes and early forms of hierarchy. Historical access to domesticable transport animals also continued to matter in the long run: Pre-industrial ethnic groups living in regions historically home to domesticable transport animals were more involved in trade and had built more complex hierarchical structures. Moreover, these groups developed greater numerical skills, larger levels of labor specialization, and higher levels of class stratification, thus underscoring the broad cultural and developmental impacts exerted by historical access to domesticable transport animals.
Keywords: F10; N30; N70; O10; Z10; 330; Domestication; hierarchy; long-distance trade; persistence